Political accountability - Bellamy, Richard (ed.); Palumbo, Antonino (ed.) (Surrey, 2010)
Political accountability is a cornerstone of representative democracy. It represents the umbilical cord that connects citizens to their representatives. Its relevance is manifold. First, it establishes the channels of communication needed to legitimate the decision-making process and its outcomes. Second, it sets the side-constraints necessary for making representative institutions responsive to citizens' wishes. Third, it also ensures the transmission of legitimate authority to the executive and administrative branches of government and helps maintain under scrutiny the activities of unelected officials and civil servants. In short, political accountability is responsible for directing the political system towards the public interest and engendering the principles of social autonomy and political self-determination at the core of democratic politics. Notwithstanding its theoretical relevance, the evolution of actual existing democracies, with their large, centralized governments, has conspired to progressively undermine the ability of citizens to keep their representatives accountable and their political regimes responsive. Far from reversing this trend, the reforms carried out by neo-liberal governments since the 1980s have increased the accountability gap. Globalization and the alleged passage from government to governance have, if anything, aggravated the problem further and started current debates about the inception of a post-democratic age.
Keywords: Government accountability